Mathematical model of rock stress under abrasive slurry jet impact based on contact mechanics. (July 2018) - Wang, Fengchao; Zhou, Dapeng; Xu, Qiwen; Qiang, Chiheng; Guo, Chuwen
Abstract: With development of water jet technology, abrasive water jet (AWJ) has become a new tool for cutting hard rock, which is widely used in stone processing, tunneling, and mining. Abrasive slurry jet (ASJ) is superior to AWJ in its ability and efficiency of rock cutting and breaking due to the addition of high-polymer. However, the stress field of rock impacted by ASJ directly affects the cutting and breaking efficiency, but there is no unified microscopic mechanism of rock failure under ASJ impact due to the uncertain contact type between the rock and the abrasive particles. In this paper, contact mechanics is used to establish a new mathematical model of rock stress under ASJ impact, which shows the rock stress distribution. Moreover, the mathematical model was solved numerically and presented in a rectangular coordinate system, from which the rock stress concentration area and failure type can be obtained. The results show that rock stress concentration appears at four areas (the center, edge, axis of particle indentation, and the edge of slurry jet), where rock is apt to be broken with axial compressive failure, radial tensile failure, shear failure, and radial tensile failure, respectively. Moreover, the rock stress caused by abrasive particle impact is much larger than that by slurry jet impact.